Allochthonous Allelopathy. Effects of Empetrum nigrum chemical interference on plant development - Pilsbacher, Anna Katharina (UiT Norges arktiske universitet, 2016)
The dwafshrub Empetrum nigrum uses phenolic compounds exuded by its leaves to depress the germination and growth of its surroundings. The allelopathic effect has, only been studied in areas immediately surrounding the plant (autochthonous allelopathy) but not in an open system apptoach that takes into account that a multitude of EMpetrum nigrum leaves get introduced into new environments through wind, rain or snowmelt (allochthonous allelopathy). An observational study of 51 snowbed in Northern Norway found an accumulation of Empetrum nirgrum leaves on every one and in 96% of examined plots. A growth and germination study grew 10 plant species native to either heath or snowbeds in soils mixed with varying concentrations of Empetrum nigrum leaves.Germination success was found to be mainly species specific and unaffected by leaf abundance for all but the highest concentration. Plant height and secondary leaf development continuously (p=>.0001 for height and leaf number) decreased with increasing abundance of Empetrum leaves in the soil, the decrease being most pronounced between the control group and plants at the lowest concentration suggesting a threshold effect. The results suggest that the subsidy of allochemicals derived from Empetrum nigrum leaves into areas previously unaffected by the plant could lead to ecosystem degradation in those environments. This is especially pertinent to snowbed environments that already face environmental stress in terms of a warming climate.